Penerapan Aplikasi “Aqua Hatch” Sebagai Media Analisa Kondisi dan Penjadwalan Pakan Pada Budidaya Ikan Koi di “Budi Daya Koi WIB” - Harry Soepandi; Dwi Wijonarko; Katarina Leba; Anang Andrianto (Fakultas Teknik Universitas Cenderawasih, 2023)
The ornamental koi fish or nishikigoi is one of the ornamental fish that is in great demand because of its beautiful body shape and color, and is believed to bring profits by koi lovers in Indonesia. The ornamental koi fish commodity has succeeded in improving the community's economy and making it an alternative source of income besides rice. Farmers and koi cultivators in the area are formed in farming groups so that their production results are well organized even though the cultivation method used so far is still traditional. There are several difficulties experienced by farmers in analyzing the condition of fish in the koi fish ecosystem, scheduling feeding, and proper maintenance methods according to the type of koi fish. In an effort to increase the effectiveness of feed management, the